(untitled) (Bioscience Journal, 2017)
This work aimed to analyze possible differences in growth patterns on Eucalyptus species and to identify the determinants climatic variables on the growth. We evaluated six Eucalyptus species (Eucalyptus camaldulensis, Eucalyptus grandis, Eucalyptus urophylla, Eucalyptus saligna, Corymbia citriodora and Eucalyptus globulus) and a Clone (GG100) implanted in an experimental arrangement of randomized blocks. We collected the collar diameter and height of all plants monthly in the course of a year, in addition to climate data (minimum temperature, maximum and rainfall). Sequentially, we obtained the correlations between the current monthly increments (collar diameter and height) and climatic variables (minimum temperature, maximum and rainfall). The Current Monthly Increment of the Collar diameter (CMI D) was not correlated to the climatic variables evaluated and the Current Monthly Increment of the Height (CMI H) was strongly correlated to the minimum temperature for the species E. camaldulensis, C. citriodora, E. saligna, E. urophylla, E. grandis and the GG100 Clone. The Rainfall showed positive correlations regarding the CMI H only for the Clone (GG100) and E. urophylla. Finally, the species E. camaldulensis, E. urophylla, E. grandis, E. saligna presented a mortality rate under 10% which is recommended according to the silvicultural criteria.